2023
DOI: 10.1371/journal.pone.0289319
|View full text |Cite
|
Sign up to set email alerts
|

Identifying adolescents’ gaming preferences for a tobacco prevention social game: A qualitative study

Abstract: Introduction Considering the dangers of adolescent tobacco use, the successful design of behavioral programs is crucial for tobacco prevention. According to preliminary research, social game interventions can improve adolescent tobacco outcomes. The current qualitative study aims to (1) uncover the gaming elements that adolescents deem important for a positive learning experience, and (2) confirm these gaming elements with adolescents who are presented with a tobacco prevention game concept that applies these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…With social gaming, Storm-Heroes relies on the social learning theory by promoting interpersonal discussions and boosting self-efficacy through the practice of skills to stay tobacco-free. Additionally, Storm-Heroes conveys normative feedback, influencing adolescents' risk perceptions regarding tobacco use [21]. This aligns with the health beliefs model, which posits that psychosocial factors such as social interaction and peer pressure can promote risk perception and ultimately encourage behavior change [22].…”
Section: A Social Game-based Interventionmentioning
confidence: 65%
See 3 more Smart Citations
“…With social gaming, Storm-Heroes relies on the social learning theory by promoting interpersonal discussions and boosting self-efficacy through the practice of skills to stay tobacco-free. Additionally, Storm-Heroes conveys normative feedback, influencing adolescents' risk perceptions regarding tobacco use [21]. This aligns with the health beliefs model, which posits that psychosocial factors such as social interaction and peer pressure can promote risk perception and ultimately encourage behavior change [22].…”
Section: A Social Game-based Interventionmentioning
confidence: 65%
“…In addition, along with other theoretical frameworks, the program design is grounded in the health belief model and empowerment theory, promoting perceived susceptibility [41] and self-efficacy [42,43]. The game-based social activities in Storm-Heroes allow adolescents to engage in interactive learning experiences that empower them to recognize and internalize the harms of tobacco, motivating them towards tobacco-free lifestyles [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Validation studies conducted on educational games often highlight the importance of user feedback in fine-tuning game mechanics and content [35]. Studies using board games have found a reduction in depression in institutionalized elderly [36], improvement in cognitive capacity in Alzheimer's patients [37], promotion of healthy eating, smoking cessation, and safer sexual practices [38].…”
Section: Discussionmentioning
confidence: 99%